Taxonomic and nomenclatural notes on Andryala glandulosa subsp. cheiranthifolia (Cichorieae, Asteraceae) from Madeira Island, Portugal - Ferreira, Maria Zita; Fernández, Inés Álvarez; de Sequeira, Miguel Menezes (Phytotaxa, 2023)
Currently two subspecies of Andryala glandulosa endemic to Madeira (Portugal) are recognized: A. glandulosa subsp. glandulosa and A. glandulosa subsp. cheiranthifolia. A thorough revision of both taxonomical and nomenclatural aspects led us to the conclusion that the subspecific epithet cheiranthifolia was misapplied. Thus, we suggest to synonymize Andryala glandulosa with A. cheiranthifolia and accept A. glandulosa as the correct name for the taxon presently known as A. glandulosa subsp. glandulosa. The taxon currently recognized as A. glandulosa subsp. cheiranthifolia exhibits distinct vegetative and reproductive structures when compared to A. glandulosa subsp. glandulosa and should, therefore, be treated as a separate species, for which the name A. subglabrata is hereby proposed. A detailed description and illustration of A. subglabrata are provided and its lectotype is designated. Diagnostic characters are discussed and compared with those of A. glandulosa.